Meta-analysis on the association of population size and life history with inbreeding depression in plants - Angeloni, F; Ouborg, N; Leimu, R (2011)
Inbreeding is common in plants and can have considerable effects on population viability, because of inbreeding depression. Understanding what determines the magnitude of inbreeding depression is of fundamental importance for conservation biology. We used meta-analysis of 116 studies and 107 plant species to investigate the effects of population size, test environment, life history characteristics and stage on the magnitude of inbreeding depression in 13 different fitness traits. We found that inbreeding depression levels significantly increase with population size. This may be a consequence of either, or both, a higher baseline of the level of inbreeding or increased impact of purging in small populations; unfortunately the available data did not allow distinguishing between these potential explanations. In general, inbreeding depression was found to be common across species and environments, and was significant in all traits examined. Yet, the magnitude of inbreeding depression was significantly influenced by plant longevity and life-history stage, and varied depending on how plant fitness was measured. Our findings highlight the fundamental role of population size in influencing the magnitude of inbreeding depression in plants. This clearly has important implications for conservation biology. Moreover, our findings on the overall generality of inbreeding depression confirm that inbreeding depression is one of the key factors reducing plant population fitness and viability. Hence, we need a better understanding on the architecture of inbreeding depression, how different ecological and historical conditions influence the levels of inbreeding depression in natural plant populations, and its impacts on community dynamics. © 2010 Elsevier Ltd.